A nano silicon-carbon composite material and preparation method thereof

The preparation of nano-silicon carbon composite materials by reacting ball milling method solves the problems of low efficiency and high cost of existing materials in lithium-ion battery applications, and achieves efficient and stable battery performance and the effect of reducing production costs.

CN115275124BActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110474922.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-29
Publication Date
2025-03-11
Estimated Expiration
2041-04-29

AI Technical Summary

Technical Problem

In the application of lithium-ion battery, existing nano-silicon-carbon composite materials have problems such as low efficiency, poor cycle stability, high cost and unsuitable preparation process for industrial production.

Method used

Nanosilicon-carbon composite materials were prepared by reactive ball milling method, and nanosilicon-carbon composite materials with multi-layer buffer structure were formed by alloy silicon etching, ball milling with LiOH·H2O mixed with calcination and pyrolysis.

Benefits of technology

It improves the first Coulomb efficiency and long cycle stability of lithium-ion batteries, reduces production costs, and makes the process more suitable for industrial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275124B_ABST
    Figure CN115275124B_ABST
Patent Text Reader

Abstract

The present disclosure provides a method for preparing a nano silicon-carbon composite material, the method comprising: S1, etching alloy silicon with an acid solution, washing and drying, obtaining alloy etched silicon; mixing the alloy etched silicon with LiOH·H2O and performing a first ball milling to obtain a nano silicon material; S2, mixing the nano silicon material with a first carbon source and performing a second ball milling to obtain a nano silicon-carbon material; S3, mixing the nano silicon-carbon material with a second carbon source and performing calcination and pyrolysis; the first carbon source is graphite; the second carbon source is selected from at least one of asphalt, petroleum coke and needle coke. When the nano silicon-carbon composite material disclosed in the present disclosure is used as a negative electrode material for lithium-ion batteries, it can effectively solve the problems of low first coulomb efficiency, poor cycle stability, high cost, and preparation process not suitable for industrial production of existing nano silicon-carbon composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion battery materials, and in particular, to a nano-silicon-carbon composite material and a preparation method thereof. Background Art

[0002] Since entering people's daily lives, lithium-ion batteries have become one of the most important chemical power sources today due to their advantages such as high energy density, high operating voltage, low self-discharge rate and safe use. The performance of lithium-ion batteries, especially the energy density, depends largely on the selection of electrode materials. Among the negative electrode materials, the theoretical specific capacity of commercial graphite negative electrode materials is only 372mAh / g. The research and development of negative electrode materials with a commercial specific capacity of more than 1000mAh / g is of great significance to improving the specific capacity of lithium-ion batteries.

[0003] The biggest problem that hinders the commercialization of silicon materials as negative electrode materials for lithium-ion batteries is the serious volume expansion effect that occurs during the charge and discharge cycle. In order to solve this problem, many innovative and representative methods have been proposed, among which nano-silicon and silicon-based composite materials are effective methods widely recognized by scholars from all walks of life. The methods for preparing nano-silicon particles are currently more commonly used, mainly chemical vapor deposition, plasma condensation evaporation, magnesium thermal reduction and mechanical ball milling. The nano-silicon spheres prepared by chemical vapor deposition are evenly distributed and have excellent performance, but the preparation process has strict requirements on the required environment and equipment. Silane (SiH4) as a silicon source is an extremely flammable and explosive high-risk gas. This high-risk and high-cost preparation method is not suitable for large-scale production to reduce costs. Therefore, this type of silicon-based negative electrode material cannot become the next generation of lithium-ion battery negative electrode materials. The preparation process required by the plasma condensation evaporation method is complex, the operation steps are cumbersome, the preparation cost is high, and it is also not suitable for large-scale production. The magnesium thermal reduction method requires the original silicon material to be processed at high temperature, which consumes a lot of energy and has low energy efficiency.

[0004] The ball milling method is a very economical method for preparing nano silicon particles. It is easy to scale up and suitable for large-scale industrial production. The ball milling method is to increase the surface defects of silicon particles and continuously refine the particles by mechanical stress generated by the continuous collision between silicon raw materials and ball milling beads and ball milling jars. However, as the ball milling time increases, after the silicon particles are refined to a certain extent, their particle size is difficult to continue to decrease, and due to the increase in specific surface area, agglomeration is also likely to occur.

[0005] At the same time, in order to solve the problem that nano-silicon negative electrode materials are easily oxidized and have poor conductivity, and to alleviate the problem that nano-silicon is active and easy to react with aqueous binders, it is necessary to carbon-coat or oxide-coat the nano-silicon particles obtained by reaction ball milling. Previous studies have shown that dispersing silicon in another electrochemically active or inactive material and using this material to buffer the volume change of silicon can, to a certain extent, block the aggregation of silicon particles during the cycle and maintain the overall stability of the electrode. At the same time, this material can also provide fast electron transmission and ion diffusion to achieve better rate performance. As a very reliable matrix material, carbon material can buffer and regulate the volume change of silicon active materials during the charge and discharge process, thereby preventing the pulverization and shedding of electrode materials. However, most of the carbon-coated materials reported so far have weak binding forces on silicon particles or lithium-silicon alloys produced by lithium insertion and extraction, resulting in problems such as easy agglomeration of silicon particles after multiple charge and discharge cycles and low electrical contact area between silicon and carbon coating, which leads to poor conductivity of silicon materials. Therefore, studying how different types of carbon coating methods can improve the electrochemical performance of nano-silicon coating will be of great benefit to the research on existing silicon negative electrode systems.

[0006] In summary, the ball milling method for preparing carbon-coated nano-silicon materials has the advantages of simple process, low cost, easy doping and industrialization. However, the existing ball milling method for preparing carbon-coated nano-silicon still has the problems of high energy consumption and long time consumption, and the electrochemical performance of carbon-coated nano-silicon materials still needs to be further improved. Summary of the invention

[0007] The purpose of the present invention is to provide a lithium ion battery nano silicon-carbon composite negative electrode material with a simple preparation method and excellent electrochemical performance and a preparation method thereof.

[0008] In order to achieve the above object, the first aspect of the present disclosure provides a method for preparing a nano-silicon-carbon composite material, the method comprising:

[0009] S1, etching the alloy silicon with an acid solution to remove the metal, then washing and drying to obtain alloy etched silicon; mixing the alloy etched silicon with LiOH·H2O and performing a first ball milling to obtain a nano-silicon material;

[0010] S2, mixing the nano-silicon material with a first carbon source and performing a second ball milling to obtain a nano-silicon-carbon material;

[0011] S3, mixing the nano silicon-carbon material with a second carbon source and then calcining and pyrolyzing the mixture;

[0012] The first carbon source is graphite; the second carbon source is selected from at least one of asphalt, petroleum coke and needle coke.

[0013] Optionally, in step S1, the silicon content in the alloy silicon is 40-80wt%, preferably 50-60wt%; the mass ratio of the alloy etching silicon and LiOH·H2O is (1-20):1, preferably (5-10):1.

[0014] Optionally, the mass ratio of the nano-silicon material to the first carbon source is (1-5):1; the mass ratio of the nano-silicon carbon material to the second carbon source is (1-4):1.

[0015] Optionally, in step S1, H + The concentration is 1-12 mol / L; the acid solution is selected from at least one of hydrochloric acid solution, sulfuric acid solution, oxalic acid solution, phosphoric acid solution, methanesulfonic acid solution, aminosulfonic acid solution and citric acid solution; the metal in the alloy silicon is selected from at least one of aluminum, iron, magnesium and titanium.

[0016] Optionally, in step S1, the etching conditions include: relative to 1g of the alloy silicon, the amount of the acid solution is 2-40mL; and the etching time is 5-60min.

[0017] Optionally, the first ball milling, the second ball milling and the calcination pyrolysis are performed in an inert atmosphere, and the inert atmosphere is selected from at least one of argon, nitrogen and helium.

[0018] Optionally, in step S1, the conditions for the first ball milling include: a ball milling speed of 300-500 rpm, a ball milling time of 6-48 hours, and a ball-to-material ratio of (10-20): 1; in step S2, the conditions for the second ball milling include: a ball milling speed of 300-500 rpm, a ball milling time of 1.5-4 hours, and a ball-to-material ratio of (10-20): 1; in step S3, the conditions for calcination and pyrolysis include: a calcination temperature of 800-1000°C, and a calcination time of 1.5-4 hours.

[0019] Optionally, the method further comprises: introducing a carbon-containing gas during the calcination and pyrolysis process; the carbon-containing gas is selected from at least one of methane, ethylene and acetylene; the flow rate of the carbon-containing gas is 100-150 mL / min, and the ventilation time is 10-30 min.

[0020] A second aspect of the present disclosure provides a nano-silicon-carbon composite material, which includes a nano-silicon-carbon core and an amorphous carbon material coated on the surface of the nano-silicon-carbon core, wherein the nano-silicon-carbon core includes silicon-based particles and graphite buffer particles filled between the silicon-based particles.

[0021] Optionally, the silicon content of the nano-silicon-carbon composite material is 10-45wt%, and the carbon content is 55-90wt%; the particle size of the nano-silicon-carbon composite material is 50-500nm.

[0022] A third aspect of the present disclosure provides a negative electrode for a lithium-ion battery, comprising a current collector and a negative electrode material coated on the current collector, wherein the negative electrode material contains the nano-silicon-carbon composite material prepared by the above method.

[0023] Through the above technical solution, the nano silicon-carbon composite material provided by the present disclosure adopts a simple reaction ball milling method to prepare nano silicon, with silicon nanoparticles as the core layer, and adopts a multi-layer buffer structure design. When the nano silicon-carbon composite material disclosed by the present disclosure is used as a negative electrode material for lithium-ion batteries, it can effectively solve the problems of low first coulomb efficiency, poor cycle stability, high cost, and preparation process not suitable for industrial production of existing nano silicon-carbon composite materials.

[0024] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0026] Figure 1 This is a scanning electron microscope photo of the nano-silicon-carbon composite material prepared in Example 2;

[0027] Figure 2 This is a scanning electron microscope photograph of the silicon aluminum alloy particles after etching in Example 1;

[0028] Figure 3 This is a scanning electron microscope photo of the nano-silicon carbon material prepared in Example 1;

[0029] Figure 4 The XRD pattern of the nano silicon carbon material prepared in Example 1;

[0030] Figure 5 The first charge and discharge curve of the lithium-ion battery prepared according to the method of Test Example 2;

[0031] Figure 6 The cycle performance curve of the lithium-ion battery prepared according to the method of Test Example 2;

[0032] Figure 7 This is a scanning electron microscope image of the silicon-carbon material prepared according to Comparative Example 1. DETAILED DESCRIPTION

[0033] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0034] A first aspect of the present disclosure provides a method for preparing a nano-silicon-carbon composite material, the method comprising:

[0035] S1, etching the alloy silicon with an acid solution to remove the metal, then washing and drying to obtain alloy etched silicon; mixing the alloy etched silicon with LiOH·H2O and performing a first ball milling to obtain a nano-silicon material;

[0036] S2, mixing the nano-silicon material with a first carbon source and performing a second ball milling to obtain a nano-silicon-carbon material;

[0037] S3, mixing the nano silicon-carbon material with a second carbon source and then calcining and pyrolyzing the mixture;

[0038] The first carbon source is graphite; the second carbon source is selected from at least one of asphalt, petroleum coke and needle coke.

[0039] The present invention adds a small amount of LiOH·H2O in the first ball milling process, and uses chemical reactions to make silicon particles produce more defects and pore structures, and promotes the first ball milling to be fully carried out to achieve nano silicon material particles of appropriate size. The addition of LiOH·H2O can, on the one hand, first react as a reactant with SiO2 on the surface of silicon particles, so that the oxygen content in the nano silicon material obtained by ball milling is reduced, thereby reducing the consumption of Li in the first cycle to improve the first coulomb efficiency; on the other hand, LiOH·H2O can react with alloy etched silicon in the ball milling process to produce lithium silicate salts such as Li2Si2O5, and the generated stress is used to promote the full progress of ball milling, so that the particle size of the obtained nano silicon particles is reduced. At the same time, the surface of the nano silicon particles prepared in the first ball milling process of the present invention has certain defects and porous structures, which reserves space for the expansion of silicon, thereby improving the cycle performance and service life of the battery.

[0040] The nano silicon-carbon composite material prepared by the present disclosure has a multi-level buffer coating layer, specifically including a nano silicon-carbon core and an amorphous carbon layer coated on the surface of the nano silicon-carbon core, wherein the silicon-based particles in the nano silicon-carbon core are filled with graphite buffer particles. Preferably, a small amount of lithium silicate particles are also attached to the surface of the silicon-based particles of the present disclosure, further enhancing the conductivity of the nano silicon-carbon composite material. When the nano silicon-carbon composite material is used as a negative electrode material, it can not only ensure the high capacity and first coulomb efficiency of the battery, but also effectively improve the long cycle stability of the battery.

[0041] Preferably, the second carbon source is asphalt. The asphalt used in the present disclosure may be petroleum-based asphalt and / or coal-based asphalt, preferably coal-based asphalt.

[0042] According to the present disclosure, in step S1, the silicon content in the alloy silicon can be 50-80wt%, preferably 50-60wt%; in order to make LiOH·H2O and the alloy etching silicon fully react, the mass ratio of the alloy etching silicon and LiOH·H2O can be (1-20):1, preferably (5-10):1.

[0043] According to the present disclosure, the silicon particles in the nano silicon carbon material prepared by reactive ball milling can reach the nanoscale, and can form a structure in which the nano silicon particles fill the gaps in the graphite particles. After being coated with pyrolysis asphalt, the silicon particles and the graphite are well coated with amorphous carbon, making the bond between Si and graphite tighter, which is beneficial to alleviate the volume expansion of the silicon particles and improve the conductivity of the composite material. As a preferred embodiment of the present disclosure, the mass ratio of the nano silicon material to the first carbon source can be (1-5):1; the mass ratio of the nano silicon carbon material to the second carbon source can be (1-4):1.

[0044] According to the present disclosure, in order to fully remove the metal in the alloy silicon, in step S1, the H + The concentration can be 1-12 mol / L; the acid solution can be well known to those skilled in the art, for example, it can be selected from at least one of hydrochloric acid solution, sulfuric acid solution, oxalic acid solution, phosphoric acid solution, methanesulfonic acid solution, aminosulfonic acid solution and citric acid solution; the alloy silicon used in the present invention can be well known to those skilled in the art, for example, the metal in the alloy silicon can be selected from at least one of aluminum, iron, magnesium and titanium, and the particle size of the alloy silicon can be 0.01-10 mm.

[0045] Furthermore, in step S1, the etching conditions may include: relative to 1g of the alloy silicon, the amount of the acid solution is 2-40mL; and the etching time is 5-60min.

[0046] In a preferred embodiment of the present disclosure, the first ball milling, the second ball milling and the calcination pyrolysis are carried out in an inert atmosphere, and the inert atmosphere can be selected from at least one of argon, nitrogen and helium.

[0047] According to the present disclosure, in step S1, the conditions for the first ball milling may include: a ball milling speed of 300-500 rpm, a ball milling time of 6-48 hours, and a ball-to-material ratio of (10-20): 1; in step S2, the conditions for the second ball milling may include: a ball milling speed of 300-500 rpm, a ball milling time of 1.5-4 hours, and a ball-to-material ratio of (10-20): 1; the material of the ball milling jar and the ball milling beads used in the first ball milling and the second ball milling in the present disclosure may be stainless steel, agate or zirconia.

[0048] According to the present disclosure, in step S3, the conditions for calcination and pyrolysis may include: a calcination temperature of 800-1000° C. and a calcination time of 1.5-4 hours.

[0049] As a preferred embodiment of the present disclosure, in order to solve the problem of incomplete coating caused by pores generated by the escape of light components of asphalt pyrolysis, the method may also include: introducing carbon-containing gas during the calcination and pyrolysis process, and making the carbon coating layer on the surface of the nano-silicon-carbon composite material more completely coated by a carbon deposition method. The carbon-containing gas used in the present disclosure can be well known to those skilled in the art, for example, it can be selected from at least one of methane, ethylene and acetylene; the introduction flow rate and introduction time of the carbon-containing gas can be adjusted according to actual conditions, for example, the introduction flow rate of the carbon-containing gas can be 100-150mL / min, and the ventilation time can be 10-30min.

[0050] A second aspect of the present disclosure provides a nano-silicon-carbon composite material, which includes a nano-silicon-carbon core and an amorphous carbon material coated on the surface of the nano-silicon-carbon core, wherein the nano-silicon-carbon core includes silicon-based particles and graphite buffer particles filled between the silicon-based particles.

[0051] The silicon-based particles disclosed in the present invention have a porous structure, which reserves space for the expansion of silicon; the graphite buffer particles filled between the silicon-based particles and the amorphous carbon coating on the surface form a multi-level buffer structure, which can effectively reduce the expansion of the negative electrode and increase the service life of the battery. Preferably, a small amount of lithium silicate salt particles are also attached to the surface of the silicon-based particles disclosed in the present invention, which reduces the consumption of Li in the first cycle, further enhances the conductivity of the nano-silicon-carbon composite material, and effectively improves the first coulomb efficiency of the lithium-ion battery. When the nano-silicon-carbon composite material disclosed in the present invention is used as a negative electrode material for a lithium-ion battery, the first coulomb efficiency of the lithium-ion battery can reach more than 90%, and can effectively improve the long-cycle stability and ensure the high capacity of the battery, and has good comprehensive performance.

[0052] According to the present disclosure, the silicon content of the nano-silicon-carbon composite material may be 10-45wt%, and the carbon content may be 55-90wt%; the particle size of the nano-silicon-carbon composite material may be 50-500nm.

[0053] A third aspect of the present disclosure provides a negative electrode for a lithium-ion battery, comprising a current collector and a negative electrode material coated on the current collector, wherein the negative electrode material contains the nano-silicon-carbon composite material prepared by the above method.

[0054] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources. Among them, the silicon aluminum alloy with a Si content of 60wt% used in the examples of the present disclosure was purchased from Changling Catalyst Company, and the particle size of the silicon aluminum alloy was 0.01-10mm.

[0055] Example 1

[0056] The Si-aluminum alloy with Si content of 60wt% was treated with an excess concentration of 1 mol L -1 Etching with hydrochloric acid, with an acid solution dosage of 25 mL relative to 1 g of the alloy silicon; etching time of 15 min, filtering after sufficient reaction, washing with deionized water until the filtrate is close to neutral, drying in a vacuum oven at 60°C for 12 hours, and obtaining etched silicon aluminum alloy particles. Take 5 g of etched crude silicon and 1 g of LiOH·H2O and place them in a zirconia ball mill for the first ball milling to obtain nano silicon material. The ball mill is first evacuated and then filled with argon for protection, the ball-to-material ratio of the ball mill is 10:1, the diameters of the zirconium balls are 5.5 mm, 3.0 mm, and 2.0 mm, and the ratio is 2:5:3, the ball milling time is 12 hours, and the ball milling speed is 450 rpm.

[0057] After the first ball milling, 5 g of natural graphite was added and the material was milled again for 1 hour under the same conditions to obtain nano silicon carbon material.

[0058] Take the nano-silicon-carbon material obtained by the reaction ball mill and the asphalt in a mass ratio of 3:1, grind and mix them thoroughly, and then place them in a tubular furnace and calcine at 900°C for 2 hours under a nitrogen atmosphere. The calcination process is to first heat the temperature to 250-550°C at a rate of 2°C / min for pre-carbonization, then heat the temperature to 900°C at a heating rate of 5°C / min, and then keep it warm for 2h. During the insulation period, acetylene is introduced at a flow rate of 100mL / min for 15min. After insulation, the temperature is lowered to room temperature to finally obtain the nano-silicon-carbon composite material of this embodiment.

[0059] The materials obtained during the preparation process of this example were characterized: Figure 2 This is a scanning electron microscope image of the silicon aluminum alloy particles after etching in this embodiment, and it can be observed that it has a porous aggregate structure. Figure 3 This is a scanning electron microscope photo of the nano-silicon carbon material prepared in this example. Figure 3 It can be seen that the particle size of the nano-silicon carbon material reaches 100-200 nm, and there are many depressions on the surface of the silicon particles, indicating that the reaction between LiOH and silicon may be a local reaction. Figure 4 is the XRD diagram of the nano silicon carbon material of this embodiment. Figure 4It can be seen that in addition to the crystal structure peaks of silicon and graphite carbon, the nano-silicon-carbon material obtained by reactive ball milling also has the peak of the reaction product Li2Si2O5, which confirms that Si reacts with LiOH and no impurities with other crystal structures are produced.

[0060] Example 2

[0061] The Si-aluminum alloy with Si content of 60wt% was treated with an excess concentration of 1 mol L -1 Etching with hydrochloric acid, with an acid solution dosage of 25 mL relative to 1 g of the alloy silicon; etching time of 15 min, filtering after sufficient reaction, washing with deionized water until the filtrate is close to neutral, drying in a vacuum oven at 80°C for 10 hours, and obtaining etched silicon aluminum alloy particles. Take 5 g of etched crude silicon and 0.5 g of LiOH·H2O and place them in a zirconia ball mill for the first ball milling to obtain nano silicon material. Among them, the ball-to-material ratio of the ball mill is 10:1, the diameters of the zirconium balls are 5.5 mm, 3.0 mm, and 2.0 mm, and the ratio is 2:5:3. The ball milling time is 12 hours, the ball milling speed is 450 rpm, and the ball milling tank is first evacuated and then filled with argon for protection.

[0062] After the first ball milling, 5 g of natural graphite was added and the material was milled again for 1 hour under the same conditions to obtain nano silicon carbon material.

[0063] Take the nano-silicon-carbon material obtained by the reaction ball mill and the asphalt in a mass ratio of 3:1, grind and mix them thoroughly, and then place them in a tubular furnace and calcine at 900°C for 2 hours under a nitrogen atmosphere. The calcination process is to first heat the temperature to 250-550°C at a rate of 2°C / min for pre-carbonization, then heat the temperature to 900°C at a heating rate of 5°C / min, and then keep it warm for 2h. During the insulation period, acetylene is introduced at a flow rate of 100mL / min for 15min. After insulation, the temperature is lowered to room temperature to finally obtain the nano-silicon-carbon composite material of this embodiment.

[0064] The materials obtained during the preparation process of this example were characterized: Figure 1 This is a scanning electron microscope photo of the nano-silicon-carbon composite material of this embodiment. It can be seen that the particle size is 50-500nm.

[0065] Example 3

[0066] The Si-aluminum alloy with Si content of 60wt% was treated with an excess concentration of 1 mol L -1Etching with hydrochloric acid, with an acid solution dosage of 25 mL relative to 1 g of the alloy silicon; etching time of 15 min, filtering after sufficient reaction, washing with deionized water until the filtrate is close to neutral, drying in a vacuum oven at 80°C for 10 hours, and obtaining etched silicon aluminum alloy particles. Take 5 g of etched crude silicon and 0.5 g of LiOH·H2O and place them in a zirconia ball mill for the first ball milling to obtain nano silicon material. Among them, the ball-to-material ratio of the ball mill is 10:1, the diameters of the zirconium balls are 5.5 mm, 3.0 mm, and 2.0 mm, and the ratio is 2:5:3. The ball milling time is 12 hours, the ball milling speed is 450 rpm, and the ball milling tank is first evacuated and then filled with argon for protection.

[0067] After the first ball milling, 5 g of natural graphite was added and the material was milled again for 1 hour under the same conditions to obtain nano silicon carbon material.

[0068] The nano silicon-carbon material obtained by ball milling and asphalt were fully ground and mixed in a mass ratio of 1:1, and then placed in a tubular furnace and calcined at 900°C for 3 hours under a nitrogen atmosphere. The calcination process was first heated to 250-550°C at a rate of 2°C / min for pre-carbonization, then heated to 900°C at a heating rate of 5°C / min, and then kept warm for 3 hours. After the heat preservation, the temperature was cooled to room temperature, and finally the nano silicon-carbon composite material of this embodiment was obtained.

[0069] Comparative Example 1

[0070] The Si-aluminum alloy with Si content of 60wt% was treated with an excess concentration of 1 mol L -1 For hydrochloric acid etching, the amount of acid solution used is 25 mL relative to 1 g of the alloy silicon; the etching time is 15 min, and after sufficient reaction, the filtrate is filtered and washed with deionized water until the filtrate is close to neutral, and dried in a vacuum oven at 80° C. for 10 hours to obtain etched coarse silicon particles.

[0071] 5 g of the etched crude silicon was placed in a zirconia ball mill for the first ball milling to obtain nano-silicon material. The ball-to-material ratio of the ball milling was 10:1, the diameters of the zirconium balls were 5.5 mm, 3.0 mm, and 2.0 mm, and the ratio was 2:5:3. The ball milling time was 12 hours, the ball milling speed was 450 rpm, and the ball mill was first evacuated and then filled with argon for protection.

[0072] After the first ball milling, 5 g of natural graphite was added and the second ball milling was carried out under the same conditions for 1 hour to obtain the silicon-carbon material of this comparative example.

[0073] The silicon-carbon material of this comparative example is characterized:

[0074] Figure 7 The scanning electron microscope image of the silicon-carbon material of this comparative example shows that the silicon particles obtained by ordinary ball milling are extremely uneven in size and have a relatively large particle size.

[0075] Comparative Example 2

[0076] The Si-aluminum alloy with Si content of 60wt% was treated with an excess concentration of 1 mol L -1 For hydrochloric acid etching, the amount of acid solution used is 25 mL relative to 1 g of the alloy silicon; the etching time is 15 min, and after sufficient reaction, the filtrate is filtered and washed with deionized water until the filtrate is close to neutral, and dried in a vacuum oven at 80° C. for 10 hours to obtain etched coarse silicon particles.

[0077] 5 g of the etched crude silicon was placed in a zirconia ball mill for the first ball milling to obtain nano-silicon material. The ball-to-material ratio of the ball milling was 10:1, the diameters of the zirconium balls were 5.5 mm, 3.0 mm, and 2.0 mm, and the ratio was 2:5:3. The ball milling time was 12 hours, the ball milling speed was 450 rpm, and the ball mill was first evacuated and then filled with argon for protection.

[0078] After the first ball milling, 5 g of natural graphite was added and the second ball milling was carried out under the same conditions for 1 hour to obtain a silicon-carbon material.

[0079] The silicon-carbon material obtained by the reaction ball mill and the asphalt are fully ground and mixed in a mass ratio of 3:1, and then placed in a tubular furnace and calcined at 900°C for 2 hours under a nitrogen atmosphere. The calcination process is to first heat the temperature to 250-550°C at a rate of 2°C / min for pre-carbonization, then heat the temperature to 900°C at a heating rate of 5°C / min, and then keep it warm for 2h. During the insulation period, acetylene is introduced at a flow rate of 100mL / min for 15min. After insulation, the temperature is cooled to room temperature to finally obtain the nano-silicon-carbon composite material of this comparative example.

[0080] Test Example 1

[0081] The nano-silicon-carbon composite material prepared in Example 1 was mixed with graphite in a ratio of 1:1 to obtain a mixed material, and the mixed material was mixed with carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5 to form a slurry, which was coated on a copper foil and dried to obtain an electrode sheet. The prepared electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, and a Celgard 2400 type separator was selected, and 1 mol L -1 LiPF6 (volume ratio of ethylene carbonate: dimethyl carbonate: diethyl carbonate = 1:1:1) electrolyte, add 5% fluoroethylene carbonate, assemble into button half-cells in a glove box, and use the Blue Power system to test the battery charge and discharge. The parameters are set as follows: current density is 0.1C for the first three cycles, 0.2C for the subsequent cycles, voltage range is 0.01-2.0V, and the first charge and discharge curve is as follows: Figure 5 , the cycle performance diagram is as follows Figure 6 .

[0082] The first discharge specific capacity of the nano silicon-carbon composite material prepared in Example 1 is 760.7 mA hg -1 The first charge capacity is 690.9mA hg -1 , the first coulombic efficiency is 90.83%, and the capacity retention rate after 50 cycles is 72.68%. It can be seen that the silicon-carbon composite material effectively improves the long-cycle stability while ensuring the high capacity and first coulombic efficiency of the battery, and has good comprehensive performance.

[0083] In order to prove that the negative electrode material of the lithium ion battery obtained in the present disclosure has a good charge and discharge platform, a charge and discharge test was performed on a button cell made using the negative electrode material provided in Example 1. The charge and discharge voltage curve is as follows: Figure 5 As shown. Figure 5 It can be seen that the test voltage range is between 0.01 and 2V, and the voltage platform is stable (around 0.4V).

[0084] Test Example 2

[0085] The electrochemical performance of the composite materials prepared in Examples 2 and 3 and Comparative Examples 1 and 2 was tested according to the method of Test Example 1. The results are shown in Table 1 below.

[0086] Table 1

[0087]

[0088] As can be seen from Table 1 above, the nano-silicon-carbon composite materials prepared by the method disclosed in the present invention have a high first coulomb efficiency, and can ensure a high first charge specific capacity and good cycle performance. The materials prepared in Comparative Examples 1 and 2 were not added with LiOH·H2O during ball milling, and the ball milling process was ordinary mechanical ball milling. From the scanning electron microscope photos of the obtained silicon particles ( Figure 7 ) It can be seen that under the same conditions, ordinary ball milling cannot obtain smaller nano silicon particles, and the particle size is very uneven. The battery prepared by the sample of comparative example 1 has poor cycle performance due to the volume expansion effect of large silicon particles during multiple charge and discharge cycles, resulting in the rupture and pulverization of the electrode material. Although the sample of comparative example 2 can partially alleviate the volume expansion effect of silicon particles after pitch carbon coating, the silicon particles are large, so the battery performance is still not ideal.

[0089] Therefore, the reactive ball milling disclosed in the present invention has a relatively obvious effect on promoting the reduction of silicon particle size and preparing nano-silicon. In addition, the multi-level buffer structure using carbon coating and adding graphite has a significant effect on improving the first cycle efficiency and long-term cycle stability of the battery.

[0090] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0091] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0092] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a nano-silicon-carbon composite material, characterized in that: The method includes: S1, etching the alloy silicon with an acid solution to remove the metal, then washing and drying to obtain alloy etched silicon; mixing the alloy etched silicon with LiOH·H2O and performing a first ball milling to obtain a nano-silicon material; S2, mixing the nano-silicon material with a first carbon source and performing a second ball milling to obtain a nano-silicon-carbon material; S3, mixing the nano silicon-carbon material with a second carbon source and then calcining and pyrolyzing the mixture; The first carbon source is graphite; the second carbon source is selected from at least one of asphalt, petroleum coke and needle coke; The H in the acid solution + The concentration is 1-12 mol / L; the etching conditions include: relative to 1g of the alloy silicon, the amount of the acid solution is 2-40mL; the etching time is 5-60min; In step S1, the first ball milling conditions include: a ball milling speed of 300-500 rpm, a ball milling time of 6-48 hours, and a ball-to-material ratio of (10-20):1; In step S2, the conditions of the second ball milling include: a ball milling speed of 300-500 rpm, a ball milling time of 1.5-4 hours, and a ball-to-material ratio of (10-20):

1.

2. The preparation method according to claim 1, wherein In step S1, The silicon content in the alloy silicon is 40-80wt%; The mass ratio of the alloy etched silicon to LiOH·H2O is (1-20):

1.

3. The preparation method according to claim 2, wherein The silicon content in the alloy silicon is 50-60wt%; The mass ratio of the alloy etched silicon and LiOH·H2O is (5-10):

1.

4. The preparation method according to claim 1, wherein The mass ratio of the nano-silicon material to the first carbon source is (1-5): 1; The mass ratio of the nano silicon carbon material to the second carbon source is (1-4):

1.

5. The preparation method according to claim 1, wherein In step S1, The acid solution is selected from at least one of hydrochloric acid solution, sulfuric acid solution, oxalic acid solution, phosphoric acid solution, methanesulfonic acid solution, aminosulfonic acid solution and citric acid solution; the metal in the alloy silicon is selected from at least one of aluminum, iron, magnesium and titanium.

6. The preparation method according to claim 1, wherein The first ball milling, the second ball milling and the calcination pyrolysis are performed in an inert atmosphere, and the inert atmosphere is selected from at least one of argon, nitrogen and helium.

7. The preparation method according to claim 1 or 6, wherein: In step S3, the conditions for calcination and pyrolysis include: calcination temperature of 800-1000° C., and calcination time of 1.5-4 hours.

8. The preparation method according to claim 1, wherein The method further comprises: introducing a carbon-containing gas during the calcination and pyrolysis process; The carbon-containing gas is selected from at least one of methane, ethylene and acetylene; The flow rate of the carbon-containing gas is 100-150 mL / min, and the ventilation time is 10-30 min.

9. A nano-silicon-carbon composite material prepared by the method according to any one of claims 1 to 8, characterized in that: The nano silicon carbon composite material comprises a nano silicon carbon core and an amorphous carbon material coated on the surface of the nano silicon carbon core. The nano silicon carbon core comprises silicon-based particles and graphite buffer particles filled between the silicon-based particles.

10. The nano-silicon-carbon composite material according to claim 9, wherein: The silicon content of the nano silicon-carbon composite material is 10-45wt%, and the carbon content is 55-90wt%; The particle size of the nano silicon-carbon composite material is 50-500nm.

11. A negative electrode for a lithium ion battery, comprising a current collector and a negative electrode material coated on the current collector, characterized in that: The negative electrode material contains the nano-silicon-carbon composite material according to claim 9 or 10.

Citation Information

Patent Citations

  • Preparation method of Si / graphite / C composite material for lithium ion battery

    CN104466141A

  • Porous carbon, nano silicon and carbon core shell structure material and preparation method thereof

    CN110224125A